Compensation in practice: the foundation 'Remembrance, Responsibility and Future' and the legacy of forced labour during the Third Reich - Goschler, Constantin; Brunner, José; Ruchniewicz, Krzysztof; Ther, Philipp (Berghahn Books, 2017)
Inhaltsverzeichnis: Introduction / Constantin Goschler -- The long shadow cast by Nazi forced labour : changing concepts of compensation and definitions of persecutees since 1945 / Henning Borggräfe -- The foundation "Remembrance, Responsibility and Future" 1999-2007 : the final chapter of compensation for Nazi injustice? / Benno Nietzel -- The Jewish Claims Conference and compensation for Nazi forced labour 1951-2008 / Benno Nietzel -- Compensating the rest of the world : the International Organisation for Migration (IOM) / Paul Erker -- The forced labourer payments programme in Poland : practices and perceptions / Michael Esch -- Compensation for forced labourers in the Czech Republic / Stephanie Zloch -- "We cannot allow the words of apology to sound only on gravestones" : forced labourer compensation in the Ukraine / Julia Landau -- Compensation for Nazi forced labour in post-Soviet Russia and Belarus / Tanja Penter --
Literaturangaben
"The present English-language study, based on a previous, more comprehensive German edition comprising four volumes, was therefore not commissioned by the Foundation "Remembrance, Responsibility and Future", but written according to the academic methods and criteria of the above-mentioned research group. It is, then, the product of an independent research project made possible by funding from the Foundation "Remembrance, Responsibility and Future"."--ECIP Foreword
Keywords: Stiftung "Erinnerung, Verantwortung und Zukunft; Aufsatzsammlung; Gedenken; Erinnerung; Zwangsarbeit; Nationalsozialismus; Stiftung Erinnerung, Verantwortung und Zukunft